THE ROLE OF PEER TO PEER LENDING IN FINTECH TOWARDS FINANCIAL INCLUSION IN INDONESIA - Shafa Sabilla (JURNAL DARMA AGUNG, 2023)
The rapid development of technology has impacted people's lifestyles, mainly dominated by information technology users and the demands of an increasingly fast-paced world. FinTech is a financial sector innovation that utilizes modern technology. Financial inclusion in Indonesia has surpassed the 75 percent target, according to data from the Financial Services Authority (OJK) gleaned from the results of the third National Financial Literacy Survey (SNLIK) conducted in 2019. The Indonesian government has set a 2024 deadline for achieving a 90 percent financial inclusion rate. Financial inclusion in Indonesia is the goal of this study, which examines the impact of FinTech on peer-to-peer lending services. Qualitative descriptive analysis and data collection techniques are used to provide an overview of the research results in this method. According to a new study, peer-to-peer lending in fintech can help low-income groups access financing, allowing them to grow their businesses. They are, however, constrained by a lack of formal funding. Many FinTech companies have made loans available to people from all walks of life, regardless of their financial situation. Financial inclusion will be more pronounced as a result of FinTech's presence.